2019
DOI: 10.1186/s13068-019-1374-2
|View full text |Cite
|
Sign up to set email alerts
|

Construction of consolidated bio-saccharification biocatalyst and process optimization for highly efficient lignocellulose solubilization

Abstract: Background The industrial conversion of biomass to high-value biofuels and biochemical is mainly restricted by lignocellulose solubilization. Consolidated bio-saccharification (CBS) is considered a promising process for lignocellulose solubilization depending on whole-cell biocatalysts that simultaneously perform effective cellulase production and hydrolysis. However, it usually takes a long time to reach a high saccharification level using the current CBS biocatalyst and process. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 45 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…C. thermocellum is considered one of the most promising species for highly efficient and low‐cost lignocellulose bioconversion (Lynd, et al , 2005), and mature genetic manipulation platforms have been constructed for this thermophile (Tripathi, et al , 2010; Olson and Lynd, 2012; Mohr, et al , 2013, Olson, et al , 2015; Zhang, et al , 2017). By using the developed tools, C. thermocellum recombinant strains have been constructed and employed as whole‐cell biocatalysts in lignocellulose saccharification and biofuel production (Argyros, et al , 2011; Lin, et al , 2015; Liu, et al , 2019). Thus, C. thermocellum has the potential to be used as the microbial chassis for the degradation of plastic waste at high temperature, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…C. thermocellum is considered one of the most promising species for highly efficient and low‐cost lignocellulose bioconversion (Lynd, et al , 2005), and mature genetic manipulation platforms have been constructed for this thermophile (Tripathi, et al , 2010; Olson and Lynd, 2012; Mohr, et al , 2013, Olson, et al , 2015; Zhang, et al , 2017). By using the developed tools, C. thermocellum recombinant strains have been constructed and employed as whole‐cell biocatalysts in lignocellulose saccharification and biofuel production (Argyros, et al , 2011; Lin, et al , 2015; Liu, et al , 2019). Thus, C. thermocellum has the potential to be used as the microbial chassis for the degradation of plastic waste at high temperature, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…CBS is a recently developed lignocellulose saccharification technology using cellulosome-producing bacterial cells as whole-cell biocatalysts [ 5 ]. By introducing heterologous secretory β-glucosidase (BGL) proteins to release the cellobiose inhibition to the cellulosome system [ 37 , 38 ], several biocatalysts have been developed with increasing saccharification efficiency [ 6 , 7 , 39 ]. It was reported that the substrate-to-sugar conversion ratio of the engineered C. thermocellum ∆ pyrF ::p2638-BGL could be over 75% with alkali-treated CCR as the substrate [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compared with the PEFA and SCO production from glucose, xylose metabolism is less efficient. However, according to our previous study, the glucan-to-xylan ratio in pretreated LCB biomass was usually higher than 75%:25%, and for CBS, the glucan saccharification efficiency could be similar to or higher than that of xylan [ 6 , 39 ]. Indeed, we determined that glucan accounted for up to 79% and 92% of the polysaccharides in alkali-pretreated CS and CCR, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of cellulase production, cellulose hydrolysis and sugar fermentation into a one-pot process is called a "consolidated bioprocess" strategy [2,11,37,[47][48][49][50]]. This strategy is made possible by a microorganism community that exhibits a cellulolytic activity that is able to hydrolyse glycosylic bonds of the cellulose and to use the lignocellulosic sugars for further fermentation into valuable products.…”
Section: Process Designmentioning
confidence: 99%